(untitled) (Experimental biology, 2009)
In the given work change of the maintenance of vitamin C of pregnant women and nursing rats at action of acoustic stress is shown and a possibility of their correction. Feeding of pregnant women and nursing the rats subjected to acoustic stress, balm "Vozrozhdenie" and an extract «Grape stones» raises the vitamin C maintenance in blood.